Upaya Membangun Teologi Pembebasan Indonesia: Belajar dari Konteks Siria-Irak dan Palestina - Dwiatmaja, Alb Irawan (Borneo Review, 2023)
The purpose of this article is to provide a new perspective in building theology that is appropriate to the Indonesian context. In an effort to build a distinctive Indonesian theology, the author explores the Syria-Iraq and Palestinian contexts that live in the midst of all situations and challenges in maintaining faith. John Damascus, al-Kindy al-Hasyimi, and Mitri Raheb developed a theology that fits the Syria-Iraq and Palestinian contexts. In their explanations, they present familiar terminology for the Syria-Iraq and Palestine situations, making it easier for Christians to explain the content of the Christian faith. In this way, Indonesian Christians can learn from Syrian-Iraqi and Palestinian Christians in building a Liberation theology that is uniquely Indonesian. To build a Liberation theology in Indonesia, it is necessary to pay attention to the challenges in Indonesia, namely the many cultures and religious traditions and more importantly to the issue of sectarianism or intolerance that results in violence. If the starting point for theology departs from the explanation of Jesus, there will be a clash. The Federation of Asian Bishops Conference (FABC) suggests doing theology in Asia, specifically in Indonesia, not starting with Christology but starting with Pneumatology.